2013
DOI: 10.1188/14.onf.67-76
|View full text |Cite
|
Sign up to set email alerts
|

Priorities for Oncology Nursing Research: The 2013 National Survey

Abstract: The results, together with the updates of the ONS Research Agenda, can guide ONS and ONS Foundation research and evidence-based practice initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 32 publications
(33 reference statements)
2
36
0
Order By: Relevance
“…A second limitation of this report is the relatively low, 20% survey response rate obtained from the SUO membership. While this response rate is not ideal, 20% is an acceptable response rate based on a search of the literature which demonstrates similar rates of response from other survey-based studies with rates ranging from 6.5-32% among health care providers including nurses, physicians, residents, and medical students [28-32]. The present survey may represent a self-selection bias as most respondents claimed to have a special interest in bladder cancer and thus reflects the proportion of SUO members with expertise in the field.…”
Section: Discussion and Review Of Literaturementioning
confidence: 88%
“…A second limitation of this report is the relatively low, 20% survey response rate obtained from the SUO membership. While this response rate is not ideal, 20% is an acceptable response rate based on a search of the literature which demonstrates similar rates of response from other survey-based studies with rates ranging from 6.5-32% among health care providers including nurses, physicians, residents, and medical students [28-32]. The present survey may represent a self-selection bias as most respondents claimed to have a special interest in bladder cancer and thus reflects the proportion of SUO members with expertise in the field.…”
Section: Discussion and Review Of Literaturementioning
confidence: 88%
“…Oncology nurses are central in reporting symptoms and changes in function to the provider, with the aim of ultimately improving QOL. In the 2013 Advanced Oncology Nursing Research national survey, the top priorities rated by oncology nurses were self-management interventions to improve symptom control, symptom management interventions, and interventions with technology to address symptoms (LoBiondo-Wood et al, 2014). The Oncology Nursing Society’s Putting Evidence Into Practice resources should be considered for symptoms such as depression and fatigue, the two most common symptoms presented in this review.…”
Section: Implications For Nursing Practicementioning
confidence: 99%
“…The National Coalition of Cancer Survivorship, a survivor-led cancer advocacy group, also has identified cognitive impairment as a challenge facing many cancer survivors and calls for research to address this problem. The Oncology Nursing Society Research Priority Survey identified cognitive impairment as one of the most distressing and difficult symptoms to treat (LoBiondo-Wood et al, 2014). Despite the priority, research in this area is relatively limited, with many unanswered questions regarding the prevalence and impact on survivors as well as insufficient data to guide evidence-based interventions (Vardy, Wefel, Ahles, Tannock, & Schagen, 2008;Von Ah, Jansen, Allen, Schiavone, & Wulff, 2011;Von Ah, Storey, Jansen, & Allen, 2013).…”
mentioning
confidence: 95%